2012
DOI: 10.1590/s1413-70542012000100011
|View full text |Cite
|
Sign up to set email alerts
|

Technological and sensory quality of restructured low-fat cooked ham containing liquid whey

Abstract: The use of liquid whey to replace water (at 0, 25, 50, 75 or 100%) in a restructured cooked ham formulation was studied and several technological and sensory quality properties were determined. The test results showed no statistically significant differences (P < 0.05) in weight loss attributes (cooking yield, storage loss, reheating loss and refreezing loss) and instrumental texture (TPA test) parameters. However, for CIELAB color, samples were (P > 0.05) less reddish (a* value reduction) and more grayish and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 18 publications
3
25
0
3
Order By: Relevance
“…The fresh liquid whey were added to a restructured cooked ham formulations up to 38% with similar results to products cured with conventional formulation (Dutra et al, 2012). Fluid whey addition had non-significant effect on the products lightness (L * ) and yellowness (b * ); however, when whey replaced at more than 50%, it induced lowest redness (a * ) values (Dutra et al, 2012).…”
Section: Recent Developments In Restructured Meat Productsmentioning
confidence: 67%
See 3 more Smart Citations
“…The fresh liquid whey were added to a restructured cooked ham formulations up to 38% with similar results to products cured with conventional formulation (Dutra et al, 2012). Fluid whey addition had non-significant effect on the products lightness (L * ) and yellowness (b * ); however, when whey replaced at more than 50%, it induced lowest redness (a * ) values (Dutra et al, 2012).…”
Section: Recent Developments In Restructured Meat Productsmentioning
confidence: 67%
“…Fluid whey addition had non-significant effect on the products lightness (L * ) and yellowness (b * ); however, when whey replaced at more than 50%, it induced lowest redness (a * ) values (Dutra et al, 2012). The inclusion of liquid whey as a substitute for water in the cure formulation of cooked ham had no effect on overall impression and texture (Dutra et al, 2012). Malav et al (2012) evaluated the effect of water chestnut flour on quality and storage stability of restructured chicken meat product and found that 10% water chestnut flour (1:1 hydrated) can be used as optimum level and the products were found acceptable up to 10 days at refrigerated storage.…”
Section: Recent Developments In Restructured Meat Productsmentioning
confidence: 92%
See 2 more Smart Citations
“…Studies using whey in processed meat products were conducted using concentrates and protein isolates. Few studies have evaluated the effects of the direct addition of liquid whey, which eliminates the drying expense in meat products . Dutra et al .…”
Section: Introductionmentioning
confidence: 99%